Adaptive organization in tourism promotion in the city of Makassar - Gita Susanti (Journal La Sociale, 2023)
Within the framework of Makassar, Indonesia, this qualitative study investigates adaptive organizational techniques in tourism promotion. Based on document analysis, interviews, and on-site observations, the study indicates a discernible shift in stakeholder perspectives away from conventional promotional strategies. Participants stress the necessity for adaptability and the careful balancing act needed to maintain Makassar's cultural identity while utilizing modern improvements. Stakeholders see community participation as a key motif, acknowledging the community as active participants in the promotional story. Visitors respond favorably to the promotional materials' integration of technology, yet the presence of traditional brochures presents a subtle hybrid model. Various visitor demographics emphasize the value of customized approaches, and the study's conclusions imply that Makassar's future prosperity depends on a robust, inclusive, Within the framework of Makassar, Indonesia, this qualitative study investigates adaptive organizational techniques in tourism promotion. Based on document analysis, interviews, and on-site observations, the study indicates a discernible shift in stakeholder perspectives away from conventional promotional strategies. Participants stress the necessity for adaptability and the careful balancing act needed to maintain Makassar's cultural identity while utilizing modern improvements. Stakeholders see community participation as a key motif, acknowledging the community as active participants in the promotional story. There is a clear and genuine approach to promoting tourism while incorporating technology into promotional materials. The results offer significant perspectives for Makassar and other locations attempting to manage the intricacies of the changing tourism terrain.